Comprehensive SPHYB and B3LYP‐DFT Studies of Two Types of Ferrocene. Issue 6 (3rd February 2017) - Rahnamaye Aliabad, H. A.; Chahkandi, Mohammad
Abstract : Structural and optoelectronic properties of ferrocene (FeC10 H10 ) using various exchange correlation potentials including Spin Polarized Generalized Gradient Approximation (SPGGA), Hybrid Density Functional Theory (SPHYB‐DFT), and hybrid density functional Becke3LYP are investigated. Obtained bandgap by the SPHYB‐DFT and SPGGA methods show consistency with the experiment, that are indirect and direct, respectively. The cell size effects on physical properties of ferrocene studied about two types of its lattice parameters (I andII ). The calculated results reveal that the cell size and the lattice parameters have a remarkable effect on optoelectronic and magnetic properties of ferrocene. However, there is no significant difference betweenI andII within molecular, structural and charge transitions in calculating UV/Vis spectrum. The calculated electronic absorption spectrum is in good agreement with experiment, in which two major electron‐transition bands derived from d–d (n → n*) and n → π* metal to ligand. NBO analyses show that there are strong donor‐acceptor interactions between central Fe atoms and cyclopentadienyl (Cp) rings that these results are in close agreement with contour plots of charge densities for prediction of the strong covalent bond between C and Fe. The optoelectronic properties of ferrocene predict that it can be efficiently used in the semiconductor devices. Abstract :